Reasons for delay in seeking medical care among women with Obstetric anal sphincter injuries - Banya, Francis; Lukabwe, Henry (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the reasons for delay in seeking medical care for OASIS among attendees of the Fistula Camp. Methods: A cross sectional study done at Kisiizi hospital during the EngenderHealth Fistula Care Plus camp in July 2018 involving a total of 10women who had OASIS were enrolled into the study. Information was obtained using a questionnaire and analysis was done using Microsoft excel. Results: The average period of time a woman stays with OASIS before seeking medical care was 10 years. On average, women deliver two babies following OASIS before they seek medical care. OASIS was sustained mainly during 1st and 2nddeliveries (80%), and delivering in absence of a skilled birth attendant (70%). The lack of: support from the husband (60%); funds to seek medical care (60%);and knowledge about the condition (70%); painless tear after healing (50%) are reasons for the delays. Conclusions: Reasons for the delay in seeking medical care after OASIS were lack of funds, knowledge and the awareness required to seek medical care. Recommendation is to strengthen the OASIS awareness programs in Southwestern Uganda. Keywords: care, delay, OASIS